Renewable energy and climate change - Quaschning, Volker 1969- (Wiley, 2020)
"Sales handles: -Clear overview on each state-of-the-art technology in alternative energy production. Presents correlations between use of energy and energy prices, and climate change. Provides guidance on what the reader can do to reduce their own energy waste. Full-colour figures and photographs throughout, data diagrams and simple calculations and results, and text boxes that highlight important information. International examples of renewable energy in action Market description: Primary: Students on renewable energy courses, or environment and sustainability courses. Planners, operators, financers and consultants. Secondary: Background reading for energy workers, and designers, politicians, journalists "--
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Renewable energy sources; Climatic changes; Renewable Energy; Climate Change; Énergies renouvelables; Climat; Changements; climate change; BUSINESS & ECONOMICS; Infrastructure; SOCIAL SCIENCE; General